PERFORMANCE OF MICROTUBERS OF VARIOUS POTATO CULTIVARS IN NET HOUSE - Singh, Vinay; Kumar, Dhruv; Singh, R P.; Singh, B P; Singh, Sarjeet (Potato Journal, 2013)
Microtubers of five potato cultivars were evaluated under net-house condition at CPRIC, Modipuram during 2004-05 and 2005-06 for their growth and production of minitubers. Higher germination, number and yield of progeny tubers m-2 was recorded in Kufri Bahar. Minimum mean tuber weight was recorded in Kufri Chipsona-2.